Single-Cell (Meta-)Genomics of a Dimorphic Candidatus Thiomargarita nelsonii Reveals Genomic Plasticity - Flood, Beverly E.; Fliss, Palmer; Jones, Daniel S.; Dick, Gregory J.; Jain, Sunit; Kaster, Anne-Kristin; Winkel, Matthias; Mußmann, Marc; Bailey, Jake (Frontiers in Microbiology, 2016)
The genus Thiomargarita includes the world’s largest bacteria. But as uncultured organisms, their physiology, metabolism, and basis for their gigantism are not well understood. Thus a genomics approach, applied to a single Candidatus Thiomargarita nelsonii cell was employed to explore the genetic potential of one of these enigmatic giant bacteria. The Thiomargarita cell was obtained from an assemblage of budding Ca. T. nelsonii attached to a provannid gastropod shell from Hydrate Ridge, a methane seep offshore of Oregon, USA. Here we present a manually curated genome of Bud S10 resulting from a hybrid assembly of long Pacific Biosciences and short Illumina sequencing reads. With respect to inorganic carbon fixation and sulfur oxidation pathways, the Ca. T. nelsonii Hydrate Ridge Bud S10 genome was similar to marine sister taxa within the family Beggiatoaceae. However, the Bud S10 genome contains genes suggestive of the genetic potential for lithotrophic growth on arsenite and perhaps hydrogen. The genome also revealed that Bud S10 likely respires nitrate via two pathways: a complete denitrification pathway and a dissimilatory nitrate reduction to ammonia pathway. Both pathways have been predicted, but not previously fully elucidated, in the genomes of other large, vacuolated, sulfur-oxidizing bacteria. Surprisingly, the genome also had a high number of unusual features for a bacterium to include the largest number of metacaspases and introns ever reported in a bacterium. Also present, are a large number of other mobile genetic elements, such as insertion sequence transposable elements and miniature inverted-repeat transposable elements (MITEs). In some cases, mobile genetic elements disrupted key genes in metabolic pathways. For example, a MITE interrupts hupL, which encodes the large subunit of the hydrogenase in hydrogen oxidation. Moreover, we detected a group I intron in one of the most critical genes in the sulfur oxidation pathway, dsrA. The dsrA group I intron also carried a MITE sequence that, like the hupL MITE family, occurs broadly across the genome. The presence of a high degree of mobile elements in genes central to Thiomargarita’s core metabolism has not been previously reported in free-living bacteria and suggests a highly mutable genome.